Os fundamentos e os limites do projeto das escolas cívico-militares - Vaz, Alexandro do Nascimento (2023)
The doctoral thesis "The Foundations and Limits of the Civic-Military Schools Project" was developed in the History and Historiography of Education research line and is linked to the research project "Anthropology and Education: An Analysis of the Connections between Subjectivity and Education from a Phenomenological Perspective" conducted by the advisor, Prof. Dr. Márcio Danelon. The thesis critically examines the Civic-Military Project as an educational model. The central issue of the research revolves around the suitability of this educational project, questioning whether it constitutes an effective approach in the school context. The underlying hypothesis of the research is divided into two possibilities: First, the Civic-Military Project is a viable and suitable model for Brazilian education; second, the Project does not prove to be an appropriate approach, not even being connected to education. The thesis is analytical and descriptive in nature, employing a critical approach. To achieve its objectives, the author conducted a thorough analysis of the Civic-Military Project, evaluating its principles, practices, and outcomes in the context of schools. To do so, the thesis presents in the first chapter the development of Brazilian military thought and the political and social implications of the military. In the second chapter, it introduces the Civic-Military Project, its history, and its foundations, focusing the analysis on the moral and punitive elements present in the Project. Next, in the third chapter, the thesis revisits the moral foundations of modern education as a counterpoint to the Civic-Military model. Finally, in the fourth chapter, the relationship between politics and education is analyzed, along with the consequences of the political use of education. The research suggests that the Civic-Military Schools Project presents itself as an ideologically driven, undemocratic, hierarchical, and violent model that positions the school as a vector for political and social transformation.